Utilization of Stakeholders#x2019; Satisfaction Results of Maritime University in South East Asia (Global Journal of Management and Business Research, 2020)
This study determined the level of satisfaction of the different stakeholders of Maritime University (JBLFMU-Molo) in South East Asia in the last five years (SY 2014-2015 to SY 2018- 2019). The researchers employed mixed-method by Bogdan
Keywords: utilization; stakeholders; satisfaction results; maritime university; and education